DETERMINING STOCK VALUE: RIGHT ISSUE AND CASH FLOW ANALYSIS (CASE STUDY ON COMPANIES LISTED ON THE LQ-45 OF THE INDONESIA STOCK EXCHANGE PERIOD 2021-2023) - Pasaman Silaban; Stefany Yunita Putri Harianja; Frederick Saroha Silaban (SULTANIST: Jurnal Manajemen dan Keuangan, 2026)
Study this aim for analyze influence rights issue and cash flow to mark shares in the incorporated companies in LQ45 index on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. Rights issue is a company strategy in get additional capital through publishing share new, temporary cash flow reflect ability company for fulfil obligation term short and invest in opportunity growth liquidity companies that can influence investor confidence in mark share. Research methods used is approach quantitative with panel data regression. Research sample consists of the five companies that meet the requirements criteria purposive sampling. The data used is secondary data obtained from report finance companies listed on the Indonesia Stock Exchange. Data analysis techniques were carried out with the selected random effect regression model based on Chow test, Hausman test, and Lagrange multiplier test. The results of the study indicate that rights issues have a positive and significant effect on stock value. Cash flow also has a positive and significant effect on stock value. Simultaneously, rights issues and cash flow have a significant effect on stock value. Furthermore, a significant relationship was found between rights issues and cash flow. The adjusted R-Squared value is 62.97%, meaning that 62.97% of the variation in stock value can be explained by rights issues and cash flow, while the remainder is influenced by other factors not examined in this study. This research aims to provide implications for company management in making policies related to funding and liquidity management. For investors, the results of this study can be used as a consideration in assessing the impact of rights issues and the company's financial condition on their investment decisions.